PEMBUATAN BAHAN BAKU SPREADS KAYA KAROTEN DARI MINYAK SAWIT MERAH MELALUI INTERESTERIFIKASI ENZIMATIK MENGGUNAKAN REAKTOR BATCH [Preparation of Red Palm Oil Based-Spreads Stock Rich in Carotene Through Enzymatic Interesterification in Batch-type Reactor] - . Sugiyono; Mario Wibowo; Soenar Soekopitojo; Nur Wulandari (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
Enzymatic interesterification of red palm oil (a mixture of red palm olein/RPO and red palm stearin/RPS in 1:1 weight ratio) and coconut oil (CNO) blends of varying proportions using a non-specific immobilized Candida antartica lipase (Novozyme 435) was studied for the preparation of spread stock. The interesterification reaction was held in a batch-type reactor. Two substrate blends were chosen for the production of spread stock i.e. 77.5:22,5 and 82.5:17.5 (RPO/RPS:CNO, by weight) through enzymatic interesterification in three different reaction times (2, 4, and 6 hours). The interesterification reactions were conducted at 60°C, 200 rpm agitation speed and 10% of Novozyme 435. The interesterified products were evaluated for their physical characteristics (slip melting point or SMP and solid fat content or SFC) and chemical characteristics (carotene retention, moisture content, and free fatty acid/FFA content). All of the interesterified products had lower SFC and SMP as compared to the initial blends. The SMP and SFC increased in longer reaction times. The SMP ranged from 30.8°C to 34.9°C. The carotene retention ranged from 74.80% to 81.08%, while the moisture content and FFA content increased in longer reaction times. The interesterified products had desirable physical properties for possible use as a spread stock rich in carotene.